2005
DOI: 10.1016/j.ijantimicag.2005.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between antimicrobial use and antimicrobial resistance in Gram-negative bacteria causing nosocomial infections from 1991–2003 at a university hospital in Taiwan

Abstract: This study was conducted to evaluate the relationship between antimicrobial resistance and antimicrobial use in a university hospital in Taiwan. Disk susceptibility data of Escherichia coli, Klebsiella pneumoniae, Enterobacter cloacae, Serratia marcescens, Proteus spp., Pseudomonas aeruginosa, Acinetobacter spp., Stenotrophomonas maltophilia and other non-fermentative Gram-negative bacilli causing nosocomial infections were evaluated. Data on annual patient-days and annual consumption (defined daily dose (DDD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
144
3
7

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(166 citation statements)
references
References 36 publications
12
144
3
7
Order By: Relevance
“…Signifi cant correlations between the consumption of specifi c antibiotics and resistance have been reported for Gram-negative bacteria including P. aeruginosa and Acinetobacter. 8,9,13 The rate of consumption of specifi c antibiotics is also related to the prevalence of resistance among nosocomial pathogens. 9 Examining correlations between consumption of specifi c antimicrobials and antibiotic resistance can assist in putting effective antimicrobial use policies in place in hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Signifi cant correlations between the consumption of specifi c antibiotics and resistance have been reported for Gram-negative bacteria including P. aeruginosa and Acinetobacter. 8,9,13 The rate of consumption of specifi c antibiotics is also related to the prevalence of resistance among nosocomial pathogens. 9 Examining correlations between consumption of specifi c antimicrobials and antibiotic resistance can assist in putting effective antimicrobial use policies in place in hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…En el caso de cefazolina, su penetración obedece en parte a su utilización profilác-tica en varias condiciones. El mercado de las cefalosporinas tiene un alcance mundial y se ha asociado a la emergencia de complejas resistencias hacia estos mismos compuestos en bacilos gramnegativos productores de BLEE (β-lactamasas de espectro extendido), a la aparición de Enterococcus sp resistente a vancomicina o a un mayor riesgo de candiduria para citar algunos ejemplos 3,5,19,20 . En tercer lugar, se logró identificar algunos factores que se asociaron significativamente a las variaciones observadas en el consumo de diferentes compuestos.…”
Section: Discussionunclassified
“…Una de ellas, la evaluación del consumo en Dosis Diaria Definida (DDD) por 100 días camas, que refleja cuántos pacientes cada 100 están recibiendo diariamente un tratamiento específico, ha sido ampliamente utilizada y ha permitido comparar diferentes escenarios, tendencias, asociación con resistencia y en forma más importante, el efecto de diferentes medidas de intervención [1][2][3][4][5] .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The elevation in the consumption of cephalosporines and carbapenems demonstrated a significant association with the increase in the resistance of Acinetobacter spp. to meropenem [4]. Another study carried out between 1997 and 2000 reported the association between periods of elevation of the consumption of imipenem and the increase in the resistance of Pseudomonas aeruginosa not only to this antibiotic but also to other beta-lactams such as ceftazidime and piperacilintazobactam [5].…”
mentioning
confidence: 99%